If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -14 = 5x + 12 Reorder the terms: -14 + X = 5x + 12 Reorder the terms: -14 + X = 12 + 5x Solving -14 + X = 12 + 5x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + X = 12 + 14 + 5x Combine like terms: -14 + 14 = 0 0 + X = 12 + 14 + 5x X = 12 + 14 + 5x Combine like terms: 12 + 14 = 26 X = 26 + 5x Simplifying X = 26 + 5x
| 3/10x+2/5=-4 | | y=-5/4x+27.5 | | 8-y=6 | | (3y+12)+(y+12)+41=0 | | 2(x+6)+7=19 | | 3(3w+5)=6(w-1) | | 12r-14=5(2-r) | | (z^2/6)-(z/2)-45=0 | | -9=63 | | 2(x+3)=x-9 | | -5m+12-3(m-3)=8m-(9m-2)-3m+3 | | 9x+2x-14+2=8 | | 13x^2+12x-1=0 | | 3x(6-9)= | | -(x-7)=3x | | 36x^2-(1/81) | | 2x-8=9x+4 | | -2+29-9(m-1)=9m-(8m-7)-3m+4 | | -6-9p=3p | | 12mn-30m-10n+25=0 | | 8(2x+4)=-5 | | 6a^3-2a=a^6 | | .4x-1.3x+14=-4 | | 8x+9=21 | | 9w=5w-12 | | 15+2x=3(x-9) | | a^2+2a+26=0 | | 5=k/3 | | 44=x-6 | | -63-13x=-5x+121 | | 42x-18x^2=0 | | -7.5x+3=-27 |